Trichinellosis Outbreak Caused by Meat from a Wild Boar Hunted in an Italian Region Considered to be at Negligible Risk for Trichinella. (7th August 2014) - Fichi, G.; Stefanelli, S.; Pagani, A.; Luchi, S.; De Gennaro, M.; Gómez‐Morales, M. A.; Selmi, M.; Rovai, D.; Mari, M.; Fischetti, R.; Pozio, E.
Summary The wild boar is an important source of trichinellosis for people in European countries as a large number of hunted animals escape veterinary control. In November 2012, uncooked sausages made with meat from wild boar were consumed by 38 persons in a village of the Lucca province (Tuscany region, Italy). Of them, 34 were serologically positive, 32 developed clinical signs and symptoms of trichinellosis, and two were asymptomatic. Trichinella britovi larvae were detected in vacuum‐packed sausages made with the same batch of sausages consumed raw which had been prepared with meat from wild boar hunted in the Lucca province. As no case of trichinellosis had been reported in this region during the last 20 years, the regional public health authority considered the risk for this zoonosis to be negligible and put in place a surveillance programme on Trichinella spp. in indicator animals (mainly foxes and including wild boar for private consumption), by testing only a percentage of heads. The experience from this outbreak shows that the definition of a region with a negligible risk for Trichinella infection is not applicable to wild boar and stresses the need to test all Trichinella‐susceptible wild animals intended for human consumption and to implement risk communication to consumers and hunters.